Resilience and prosperity through agro-well driven cultivation in the north central province, Sri Lanka: a case study on its evolution, structure and impacts - de Silva, Sanjiv; Curnow, Jayne; Ariyaratne, Badugodahewa Ranjith (2016)
Agricultural practices are changing at an unprecedented rate in small pockets of the dry zone of Sri Lanka. Commercial vegetable production is flourishing underwritten by groundwater accessed via agro-wells, increased market access and new business opportunities. Since the early 1990s, small-holder farmers have been excavating agro-wells for highland field irrigation and reaping unprecedented returns. Highland fields were previously subject to rain-fed shifting cultivation with long fallow periods. Water from agro-wells with the addition of chemical inputs, along with the advent of mobile phones, reliable road transport, new markets, greater access to credit and a more secure post-conflict environment, have now made frequent highland cropping viable and profitable. This has ignited the entrepreneurial spirit of farmers whose financial inputs and investments and labour is bringing rapid socio-economic transformation. In a country where the dry zone constitutes roughly a third of the land area, and where many dry zone households lack surface water for dry season cropping, these pockets of groundwater driven dry season production may pose a way out of poverty. While acknowledging the significant impact of agro-well-based farming in lifting farmers out of poverty, the paper ends on a cautionary note. This type of agricultural intensification is predicated on a social-ecological system linked to a specific institutional architecture and an aquifer with highly variable water availability. Current success in poverty alleviation masks an inherent fragility and risk that warrants further investigation before attempts are made to scale out groundwater based dry season farming to other parts of the dry zone.